Zebra stripes in the Atacama Desert revisited: granular fingering as a mechanism for zebra stripe formation? - May, Simon Matthias; Hoffmeister, Dirk; Wolf, Dennis; Bubenzer, Olaf (Geomorphology, 2019)
Although a number of studies have pointed out the remarkable slowness of Earth surface processes in the Atacama Desert, process mechanisms under such extremely limited water availability are poorly understood, and process rates remain unknown. This paper revisits the discussion on the formation of the prominent Atacama-specific hillslope zebra (stone) stripes, previously interpreted to result from palaeo-overland flow (Owen et al., 2013). Compared to this study, our data document different stripe characteristics with regard to stripe form and orientation as well as sorting- and bedding-patterns of stripe-confining surface gravel units. We found a remarkable form-concordance between zebra stripes and deposits from experiments on segregation-induced granular fingering. Hence, we propose a combination of seismic shaking and instantaneous dry granular free surface flows as the key mechanism for zebra stripe formation. Our findings underline the potential significance of seismicity in shaping Atacama landscapes, which bear important analogies to extra-terrestrial surfaces.
Gesehen am 18.10.2019